A survey of organizational culture and organizational performance in a manufacturing company - Dom, Veliswa Virginia (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
The purpose of this research was to explore the relationship between organizational culture and organizational performance in a manufacturing company. This company supplies metal products to the motor vehicle manufacturing industry, where the quality and quantity of parts produced is of paramount importance, since the buyers of these products are quality conscious. The organization has three production shifts that rotate each week. Anecdotal observations are that irrespective of the time that a shift operates over the course of the month, the different shifts tend to perform at different levels in terms of quality and quantity of output. This study therefore sought to investigate if these differences between shifts are statistically significant, and if so, whether these shifts also have differences in organizational culture. Components of organizational culture include values, norms, beliefs, attitudes, principles and expectations that give the organization a unique personality and differentiate it from other organizations. While the literature indicates that qualitative or quantitative approaches can be used in organizational culture research, this research adopted the quantitative approach, making use of the Competing Values Framework (CVF). The CVF is a four-category organizational culture typology established by Cameron and Quinn (2006). The framework is based on two dimensions: stability or flexibility of the organization, and external or internal focus. In this research, the CVF was used as a measurement tool to evaluate organizational culture. In order to determine differences in organizational culture between shifts, a survey was undertaken (N=138) which measured employee perceptions pertaining to the existing organizational culture of each of the three production shifts at the company. Secondly, differences in performance between the shifts were examined by using the performance data for a three-month period for each shift in terms of quantity and quality. This data was obtained from the management of the production process at the company. Statistical analysis was done using ANOVA to analyse the differences between the shifts. The findings indicated that the dominant existing organizational culture at the company under investigation is a clan culture. Furthermore, there is a statistically significant difference between the cultures of all the three shifts at the manufacturing company. The results also indicated that there is a statistically significant difference in the quantity and quality of production between the three shifts. In conclusion, the research indicated there are differences in culture and in performance, but given the nature of the data, it was not possible to statistically analyse the relationship between shift culture and performance. However, it is conceivable that cultural differences between shifts may be contributing to performance differences. With regards to further research, it is recommended that this research be extended to other branches of the manufacturing company in other regions, in order to determine whether there are any significant differences in culture and performance between these branches and their shifts. Research could also be extended to other South African organizations to create a sufficiently large sample of shift and/or business units, so as to be able to do statistical analysis of the relationship between culture and performance.
Keywords: Corporate culture -- South Africa -- Eastern Cape; Organizational behavior -- South Africa -- Eastern Cape; Factories -- South Africa -- Eastern Cape; Analysis of variance; Shift systems -- South Africa -- Eastern Cape; Employees -- Rating of -- South Africa -- Eastern Cape; Competing Values Framework (CVF)